AFTER DARKNESS, COMES PAUD: IMPLEMENTATION OF RA KARTINI'S LEGACIES IN TK NEGERI PEMBINA JERUKWANGI (Jurusan PGPAUD FIP UNNES, 2022)
This study was aimed at describing the implementation of R.A. Kartini’s legacies in TK Negeri Pembina Jerukwangi Jepara. The data in this study was gerenated through observation and interviews, then analyzed using Miles’ and Huberman’s model in Sugiyono (2018). The findings show that the promotion of R.A. Kartini’s legacies in TK Negeri Pembina Jerukwangi Jepara is to imitate her positive virtues and character in general such as her reading habit, hard work, caring and loving other, and non discriminatory attitude. The promotion of Kartini legalicies includes such aktivities as wearing the Jepara Javanese school uniform resembling Kartini's apparel, commemorating Kartini Day, story telling of Kartini's life, field trips to destination related to Kartini, Mareover, Kartini's legacy is also implemented as parts of institutional governance. In this respect, the promotion be seen in the development of local curricural contents. This study was aimed at describing the implementation of R.A. Kartini’s legacies in TK Negeri Pembina Jerukwangi Jepara. The data in this study was gerenated through observation and interviews, then analyzed using Miles’ and Huberman’s model in Sugiyono (2018). The findings show that the promotion of R.A. Kartini’s legacies in TK Negeri Pembina Jerukwangi Jepara is to imitate her positive virtues and character in general such as her reading habit, hard work, caring and loving other, and non discriminatory attitude. The promotion of Kartini legalicies includes such aktivities as wearing the Jepara Javanese school uniform resembling Kartini's apparel, commemorating Kartini Day, story telling of Kartini's life, field trips to destination related to Kartini, Mareover, Kartini's legacy is also implemented as parts of institutional governance. In this respect, the promotion be seen in the development of local curricural contents. Keywords: R.A. Kartini’s Legacy, Implementation, Institutional Governance.